LEXICONS IN LEGONG KERATON DANCE - Anak Agung Istri Mas Diah Utari Dewi; I Gede Budasi; I Wayan Suarnajaya (Lingua Scientia, 2020)
Legong keraton dance is a classic dance that has many lexicons to identify. Culturally, there are some lexicons in Legong Keraton dance used normally, but time by time the lexicons are less frequently used while doing the dance practices. This study aimed at finding out the lexicons that exist in Legong Keraton dance. This study was designed in form of descriptive qualitative study using ecolinguistic approach. This study focused on lexicons which exist in Legong Keraton dance at Sanggar Tari Warini in Denpasar. The obtained data were collected from observing, and interviewing. The result of the study showed that there were forty-eight lexicons exist in Legong Keraton dance, classified into: structure (four lexicons), hand movements (thirteen lexicons), leg movements (twelve lexicons), body movements (twelve lexicons), neck movements (three lexicons), eyes movements (two lexicons), and fan movements (three lexicons).